The Effectiveness Of Using Digital Storytelling Video In Teaching Speaking At SMK Telkom Banjarbaru: Efektivitas Penggunaan Digital Video Storytelling Dalam Pengajaran Berbicara di SMK Telkom Banjarbaru - Sri Endang Ratnasari (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2023)
The efficiency of using a Digital Storytelling film in the classroom to teach speaking skills by means of question-and-answer sessions was evaluated at the eleventh SMK Telkom Banjarbaru.The purpose of this study is to investigate whether or not the use of digital story telling video is beneficial in enhancing the students' ability to communicate orally. The researcher used a purposive sampling method and took only class X the sample of the research which consisted of 37 students. In addition, the researcher applied an instrument of this research namely oral test. In pre-test and post-test, the researcher gave the topics through digital storytelling video to stimulate the students to speak in their daily activity. In pre-test and post-test, one by one of the students asked to speak face to face with the researcher in the class. After pre-test, the researcher applied a media of teaching as a treatment then the result of post-test was compared with the result of the student’s pre-test and find out the improvement of the students‟ speaking ability. The findings of the data analysis revealed that the mean score on pre-tests was 3.45, while the mean score on post-tests was 4.54. These findings were based on the fact that the pre-tests were administered before the post-tests. It was discovered that the result of the t-test was 10.33, which was higher than the value of the t-table, which was 1.688. The level of significance that was used was 0.05, and the degree of freedom (df) that was used was 37-1, which equaled 36. That the alternative hypothesis was accepted while the null hypothesis was rejected was the implication of this.